Energy Price Dynamics in the Face of Uncertainty Shocks and the Role of Exchange Rate Regimes: A Global Cross-Country Analysis - António Afonso; José Alves; Jo\~ao Jalles; Sofia Monteiro (CESifo GmbH, 2024)
This study examines the effects of geopolitical risk and global uncertainty on energy prices, conditioned by different exchange rate regimes, for 185 economies over the period 1980-2023. The central question is how uncertainty impacts energy prices and whether exchange rate flexibility mediates these effects. Using panel data techniques, including OLS and Panel VAR, we assess both demand and supply-side channels, exploring country-specific differences. Our key findings indicate that uncertainty shocks significantly raise energy prices, particularly in countries with flexible exchange rates, where currency depreciation amplifies global price fluctuations. Asymmetric results are found regarding emerging markets, with flexible exchange rates, which tend to have lower energy prices, while oil-exporting countries and OPEC members experience distinct pricing dynamics. These results underscore the importance of exchange rate policy choices in shaping energy market responses to global shocks. Policymakers may need to adopt complementary measures to manage the volatility arising from global uncertainty.
Keywords: C23; E44; G32; H63; 330; geopolitical risk; world uncertainty index; global energy markets; exchange rate regimes; asymmetric effects